Kajian metode penentuan kekuatan momen retak tiang pancang spun pile - Candra Irawan; I Gusti Putu Raka; Priyo Suprobo (Institut Teknologi Sepuluh Nopember, 2020)
This paper describes the results of a study carried out experimentally on the determination of the moment strength of spun pile piles. The methods used are visual observation, load-displacement curve evaluation, and tensile strain analysis. The experimental results show that a load of data taken is a little late between 3 and 9 % compared to the results based on load-displacement curve. The crack load accuracy results from the load-deflection curve analysis were validated by the PC bar tensile strain reading. The deflection at crack read on the load-deflection curve is the same as the deflection at the start of the tensile strain jump on the PC bar.